Alpha-Melanocyte Stimulating Hormone: An Emerging Anti-Inflammatory Antimicrobial Peptide - Singh, Madhuri (Hindawi Publishing Corporation, 2014)
The alpha-melanocyte stimulating hormone (α-MSH) is a neuropeptide belonging to the melanocortin family. It is well known for its anti-inflammatory and antipyretic effects and shares several characteristics with antimicrobial peptides (AMPs). There have been some recent reports about the direct antimicrobial activity of α-MSH against various microbes belonging to both fungal and bacterial pathogens. Similar to α-MSH's anti-inflammatory properties, its C-terminal residues also exhibit antimicrobial activity parallel to that of the entire peptide. This review is focused on the current findings regarding the direct antimicrobial potential and immunomodulatory mechanism of α-MSH and its C-terminal fragments, with particular emphasis on the prospects of α-MSH based peptides as a strong anti-infective agent.